A Rare Case of Gastric Mantle Cell Lymphoma causing Superior Mesenteric Artery Syndrome in an Adult - Garg, Shailesh; Derzie, Alain (International Journal of Angiology, 2016)
Superior mesenteric artery (SMA) syndrome or Wilkie syndrome is a rare condition that arises when the distal third of the duodenum becomes trapped between the SMA and the abdominal aorta causing intestinal obstruction. It is most commonly described in adolescents and rarely in adult patients. We present an interesting case of an adult who developed SMA syndrome from an uncommon gastric mantle cell lymphoma that was recognized early and treated surgically.
Keywords: artery; mesenteric artery; symptomatic; early; immune system; ischemia; prevention